Feral cats and habitat degradation drive mammal declines in northwestern Australia: An expert elicitation to prioritize management actions - Alyson M. Stobo‐Wilson; Alys Stevens; Sarah M. Legge; Brett P. Murphy; Anna E. Richards; Chris Pavey; Kendrick Bush; Skye F. Cameron; Ben Corey; Teigan Cremona; Jill Curtis; Hugh Davies; et al. (Conservation Science and Practice)
Abstract As small (<5.5 kg) native mammals continue to decline throughout northern Australia, there is a critical need to identify the most significant threatening processes and those management actions with the greatest likelihood of alleviating them. Using a structured elicitation process, we sought to identify such management priorities by: (1) reviewing the literature since 2010 to identify a suite of potential drivers of small mammal decline; and (2) estimating the relative impacts of the putative threats and the ability to manage such threats. We reviewed 106 publications, from which we identified 11 threats and 14 threat attributes possibly contributing to the decline of small mammals in the region. From the expert elicitation, we scored and ranked each threat and threat attribute for its severity, geographic scope, potential for mitigation, and uniformity of impact across species. The elicitation suggested that the contemporary threats with the greatest relative impact on native mammals in northwestern Australia are: (1) predation by feral cats; and (2) habitat degradation by feral livestock and by inappropriate fire regimes. Tractable management actions aimed at reducing the density of feral livestock and improving fire regimes are likely to simultaneously reduce predation pressure from feral cats on small mammals and improve the availability of critical resources.